Energy Transfer Induced by Dye Encapsulation in a Hybrid Nanoparticle‐Purple Membrane Reversible Assembly. (16th August 2019) - de Q. Silveira, Gleiciani; Chen, Zhaowei; Barry, Edward F.; Diroll, Benjamin T.; Lee, Byeongdu; Rajh, Tijana; Rozhkova, Elena A.; Laible, Philip D.; Fry, H. Christopher
Abstract: The purple membrane (PM) isolated from the bacteria Halobacterium salinarum ( H. salinarum ) arranges the transmembrane proton pump bacteriorhodopsin (bR) in a 2D hexagonal crystalline lattice. Here, PM sheets containing native bR bend into tube‐like structures with open edges under acidic pH conditions. When decorated with gold nanoparticles (AuNPs), these same PM sheets yield a sealed tube assembly. Upon Rhodamine B (Rh B) sequestration inside the sealed tube, a dramatic decrease in Rh B fluorescence lifetime (τf ) from 1.5 ns (unencapsulated) to 14 ps (encapsulated) is observed. The dramatic decrease in lifetime is attributed to energy transfer between AuNPs and Rh B. Subsequent release from the AuNP–PM capsules triggered by an increase in pH shows that 93% of Rh B is recovered (τ = 14 min) due to the capsules' unfolding. The hybrid AuNP–PM material highlights the utility of multicomponent ensembles (i.e., lipid bilayer, protein array, and NPs) by demonstrating that complex, multistimuli 3D responses can lead to multiplexed functions such as controlling energy transfer in the confined, encapsulated state and breaking the energy pair via molecular release in response to a change in pH. Abstract : The reversible, pH induced tubule formation of purple membrane functionalized with gold nanoparticles (AuNPs) highlights the ability to not only reversibly encapsulate a fluorescent dye molecule, but also facilitate the material's charge transfer capability. Time resolved photoluminescence spectroscopy indicates charge transfer between the dye and the AuNPs. The lifetime of the dye recovers upon disassembly and release of the molecule.